Weldability Characteristics of Dissimilar Al/Cu Friction Stir Weld Joints - Sarsilmaz, Furkan (Carl Hanser Verlag, 2012)
In the present investigation, the AA1030 aluminium alloy and commercially pure copper plates were joined by friction stir welding. The effect of the processing parameters on the interface morphology, microstructure and strength of the joints was analyzed. The experimental results showed that some intermetallic compounds such as AlCu, Al4Cu9 and Al2Cu cause the weld to crack during the friction stir welding process on the centerline of the weld. Especially at lower traverse speeds such as 60, 90, and 125 mm/min, some tunnels and voids were detected in the Aluminium close to the Al/Cu interface. The maximum tensile strength of the samples was obtained at a traverse speed of 160 mm/min getting by without cavity defects in the weld. In addition, the fracture morphology revealed both partially brittle and cleavage-like fracture.
Keywords: Mechanical-Properties; Microstructural Evolution; Aluminum; Copper; Speed